Analysis of the Attractiveness of Tourism Destinations in Tehran - seyed komeil salehi; Habibeh Nabizadeh; amineh anjem shoa (تحقیقات کاربردی علوم جغرافیایی)
The objective of this research is to investigate the factors that enhance the attractiveness of tourism destinations in Tehran. This study is applied in nature and employs a descriptive-analytical methodology. The data collection methods include the use of questionnaires and interviews. The statistical population comprises tourism experts and specialists, and through the application of Cochran's formula and simple random sampling, a sample of 210 tourism experts was selected. Data analysis was performed utilizing descriptive statistics and logistic regression tests.  The findings of the research reveal that, out of the 210 tourism professionals in Tehran, 91 individuals, representing 43.3%, perceived the attractiveness of Tehran's tourism destinations to be at a high level; 29% assessed it as moderate; and only 27% regarded it as low. Furthermore, the results concerning the factors influencing the enhancement of attractiveness in alignment with tourism development indicate that, among the four factors considered, the most significant were: 1) innovative business opportunities, with an impact coefficient of 0.613; 2) the city's natural, cultural, and historical assets, with an impact coefficient of 0.577; 3) the development of tourism infrastructure, with an impact coefficient of 0.497; and 4) urban development, with an impact coefficient of 0.473.